APHRODISIAC EFFECTS OF METHANOLIC LEAF EXTRACT OF PSEUDOPANAX ARBOREUS (ARALIACEAE) (L.F. PHILLIPSON) IN NORMAL MALE RATS - Besong, Egbe B.; G., Ateufack; Kamanyi, Albert; Moumbock, Aurelien F.A. (African Journal of Traditional, Complementary and Alternative Medicines, 2019)
Background: The leaves of Pseudopanax arboreus have been used traditionally for decades as aphrodisiac without scientific investigation. In this study, the effects of methanolic leaf extract of P. arboreus were evaluated on sexual behavior of normal male rats. Materials and Methods: Twenty-eight adult male rats were randomly grouped into 4 groups of 7 rats each. Rats in group 1 were treated with 10 ml/kg body weight distilled water, group 2 rats received 6mg/kg body weight Viagra™, while the rats in groups 3 and 4 were given 46.5 mg and 93mg/kg body weight respectively of the methanolic extract of the leaves of P. arboreus. Female rats were made receptive by ovariectomy and subsequent hormonal treatment. Sexual behavior parameters were monitored on days 1, 7, 14 and 21 by pairing each male rat to a receptive female. Relative weight of sex organs and hormonal (FSH, LH and testosterone) profile were also determined. Results: Doses of 46.5 mg/kg and 93 mg/kg, the extract significantly increased the mount and intromission frequencies, penile licking and relative weight of sex organs and enhanced testosterone production; and significantly reduced mount and intromission latencies, mean intromission interval, when compared to the distilled water group. The 93 mg/kg body weight dose prolonged ejaculation latency and reduced post-ejaculatory interval. However, the reference drug, Viagra™ proved more efficient than the extract. Conclusion: The methanolic extract of the leaves of P. arboreus possesses aphrodisiac properties which may be due to the actions of bioactive compounds present in the extract.